Effectiveness of Mental Imagery Training in Improving Breaststroke Start Skills among Swimming Academy Athletes - Wendri Maryadi; Acep Rohmat Nurhidayat; Ahmad Rizal; Muhammad Ali Ode (MASI Mandiri Edukasi, 2026)
This study aimed to analyze the effectiveness of PETTLEP-based mental imagery training in improving breaststroke start skills among athletes at Dolphins Swimming Academy. Psychological factors play a crucial role in sports performance, particularly in time-sensitive sports such as swimming, where the start phase significantly influences race outcomes. This study employed a quasi-experimental design with a one-group pretest–posttest model involving 12 athletes aged 15–20 years. The intervention was conducted over four weeks and integrated into the regular training program. Performance indicators included reaction time and 15-meter performance as representations of start skills. The results showed significant improvements in both variables. Reaction time decreased from 0.789 seconds to 0.711 seconds, while the 15-meter time improved from 8.324 seconds to 7.744 seconds (p < 0.001). These improvements indicate enhanced anticipatory motor control, push-off efficiency, and underwater transition during the start phase. In conclusion, PETTLEP-based mental imagery training effectively improves breaststroke start skills by enhancing neuromotor readiness and psychological stability. Practically, this approach can be integrated into swimming training programs as a complementary strategy to improve start performance and overall competitive readiness.